Muscle oxygenation trends after tapering in trained cyclists - Neary, J. P.; McKenzie, D. C.; Bhambhani, Y. N. (Dynamic Medicine, 2005)
This study examined muscle deoxygenation trends before and after a 7-day taper using non-invasive near infrared spectroscopy (NIRS).